Cognitive and behavioral factors in the chronification of suicidal behavior - M. I. Subotich; A. B. Kholmogorova (Неотложная медицинская помощь, 2023)
Relevance. Suicide is one of the leading causes of death worldwide. Suicidal behavior is a complex phenomenon that includes suicidal thoughts, intentions and actions; and those actions do not always lead to death, but often turn into chronic suicidal behavior. The study of the factors in chronification of suicidal behavior is necessary for the development of evidence-based programs for the prevention of repeated suicide attempts.Aim of study. is to compare cognitive and behavioral strategies for coping with stress in patients with single suicide attempts and chronic suicidal behavior.The hypothesis of the study is that in patients with repeated suicide attempts, destructive cognitive and behavioral strategies for coping with stress are more pronounced.Materials and methods. The study included 119 patients treated at the somatopsychiatric and toxicology departments, 60 patients after the primary suicide attempt, 59 – after repeated ones. Patients were asked to complete the following procedures: Beck Depression Inventory (Beck, 1961; N.V. Tarabrina, 2001), Beck Anxiety Inventory (Beck, 1961; Tarabrina, 2001), Rumination Scale (Treynor W. et al., 2003; adaptation by O.D. Pugovkina et al., 2021), Alexithymia Scale (Toronto Alexithymia Scale G.J. Taylor et al., 1985; adaptation by Starostina E.G. et al. 2009), COPE Inventory (Ch.S. Carver et al., 1989; adaptation by P.A. Ivanov and N.G. Garanyan, 2013).Results. Patients after repeated suicide attempts, compared with patients who made the first attempt, are more likely to be diagnosed with borderline personality disorder, have more pronounced symptoms of depression and suicidal readiness, higher rates of ruminative thinking and alexithymia — reflecting a deceptive cognitive style, — as well as indicators of the use of destructive behavioral strategies for coping with stress in the form of various types of avoidance behavior.